Management of coriander wilt using biocontrol agents - Muthukrishnan, Sabitha Doraisamy, P Muthulakshmi, N Chezhiyan, K (Journal of Spices and Aromatic Crops, 2002)
A replicated field trial on biocontrol of coriander wilt caused by Fusarium oxysporum f., sp. coriander; was conducted in kharif season during 1995-96, 1996-97 and 1997-98 in the Department of Spices and Plantation Crops, Horticultural College and Research Institute, TNAU, Coimbatore. Seed treatment with Trichoderma viride at 4 g kg-1 of seed was found to be more effective in reducing the wilt incidence to 5.3 per cent as against 28.3 per cent recorded in untreated, control plots in all the three years. The mean yield (387.5 kg ha-1) for all the three years was also significantly higher in seed treatment with T. viride as against very low yield (162 kg ha-1) obtained in untreated plots. The cost benefit ratio was also enhanced with the same treatment.